Dystocia due to iniodymous conjoined twin monster fetus in a buffalo and its removal by fetotomy - Pandey, Anand Kumar; Kumar, Parveen; Kumari, Sonu; Singh, Gyan; Kumar, Sandeep; Yadav, Vishal; Kumar, Lokesh; Pareek, Manish; Sharma, Satbir (Buffalo Bulletin, 2017)
A case of dystocia due to iniodymous conjoined twin monster fetus in a buffalo was reported in the clinics. Fetotomy was performed to relieve the subsequent dystocia.